History of the Impeachment of Andrew Johnson, President of the United States, by the House of Representatives, and his trial by the Senate for high crimes and misdemeanors in office, 1868 - Ross, Edmund G. (Edmund Gibson), 1826-1907 (Salt Lake City, UT : Project Gutenberg, 2000)
"History of the Impeachment of Andrew Johnson, President of the United States,$1! =(B" by Edmund G. Ross is a historical account likely written in the late 19th century, focusing on the contentious impeachment of Andrew Johnson in 1868. This work seems to delve into the complexities surrounding Johnson's presidency, particularly in the context of the post-Civil War Reconstruction era, addressing the political dynamics between the President and Congress that culminated in impeachment proceedings. The opening of the text establishes the pivotal moment in American history marked by Johnson's impeachment. It introduces the reader to the lack of public awareness regarding the events leading to the impeachment, emphasizing the significance of this political struggle and its far-reaching consequences. The narrative highlights the challenge of reconstructing the United States after the Civil War, presenting the conflicting ideologies of leaders like Abraham Lincoln and Johnson, particularly regarding the treatment of the defeated Southern states and the integration of freed slaves into society. As it lays out the constitutional foundations of impeachment, the text sets the stage for a deeper analysis of the power struggles inherent in American governance during this turbulent period. (This is an automatically generated summary.)s
Release date is 2000-12-01
Produced by Dianne Bean and David Widger
Keywords: Johnson, Andrew, 1808-1875 -- Impeachment